Introduction to Foodborne Infections and Intoxications Subtitle: An African Perspective - Sampane-Donkor, E.; Kotey, F.C.N.; Darkwah, S.; Owusu, I.A.; Tetteh-Quarcoo, P.B.; Dayie, N.T.K.D. (Office of Research, Innovation and Development, University of Ghana, Legon, 2023)
Foodborne infections and intoxications pose a significant global health threat, especially in Africa and other low-income regions. The goal of this book is to explore the intricate web of factors that influence foodborne infections in Africa. It delves into specific aspects of food safety, providing insights into the unique challenges and opportunities that Africa presents. By integrating disciplines such as microbiology, epidemiology, veterinary medicine, public health, and food science, the textbook advocates for a multidisciplinary approach to develop effective preventive measures, surveillance systems, and interventions.
Book
Keywords: Foodborne Infections; Intoxications; Subtitle; African